Daniel Tiger's neighborhood. King Daniel for the day [videorecording (DVD)]. (Daniel Tiger's neighborhood (Television program), 2017)
Daniel is declared 'King for the Day' by King Friday, who sends him on a royal mission to Baker Aker's bakery and Music Man Stan's shop. In this tigertastic DVD, Daniel also helps celebrate Prince Wednesday's birthday, shares a book at the library with O the Owl, and takes care of the class pet!